Application of the Five Domains model to food chain management of animal welfare: opportunities and constraints - Beausoleil, N. J.; Swanson, J. C.; McKeegan, D. E. F.; Croney, C. C. (Frontiers in Animal Science, 2023)
For businesses involved in animal production, ensuring high animal welfare standards has become a cornerstone of corporate social responsibility practices. Since animal welfare cannot be verified by consumers at the point of purchase, industry-led audits provide important assurance that animals used to produce food lived an acceptable quality of life and experienced a humane death. The Five Freedoms offer a memorably simple route to conceptualize the complex, multi-dimensional phenomenon of animal welfare, and they have been widely adopted as a basic operational framework for audits. However, the Five Freedoms are problematic in that they focus on the absence of states, underemphasize the importance of positive experiences, are absolute, and represent a (mostly unattainable) ideal. The Five Domains model represents inter-related aspects of an animal’s welfare state, with four physical/functional domains used to infer likely mental experiences. This model allows for consideration of both positive and negative affective states, recognizes degrees of welfare compromise, acknowledges that animals cannot be free from all negative experiences (and that indeed, some are essential for survival), and thus, better reflects current scientific understanding of animal welfare – that ultimately, we are interested in how animals experience their lives. Nevertheless, caution is needed when inferring mental states which can never be directly observed, and hence outcomes must be qualitative. The Five Domains model can underpin both resource- and animal-based measures of welfare, which reflect welfare risks and outcomes respectively, and its operationalization offers several opportunities to improve the breadth and quality of welfare audit for production animals. Existing welfare indicators may be linked to relevant mental states and weighed accordingly, and new metrics may be identified. Since systems based on the Five Domains demand scrutiny of the affective state consequences of housing, handling and husbandry procedures, they could improve the effectiveness of animal welfare training for auditors and stockpersons. By representing a clear commitment to examining animal experience, adoption of the Five Domains could facilitate improved communication about animal welfare in the food chain with customers and consumers.